2021
DOI: 10.1140/epjc/s10052-021-09025-8
|View full text |Cite
|
Sign up to set email alerts
|

Generating solutions for charged stellar models in general relativity

Abstract: It is shown that the expressions for the tangential pressure, the anisotropy factor and the radial pressure in the Einstein–Maxwell equations may serve as generating functions for charged stellar models. The latter can incorporate an equation of state when the expression for the energy density is also used. Other generating functions are based on the condition for the existence of conformal motion (conformal flatness in particular) and the Karmarkar condition for embedding class one metrics, which do not depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…[45]. We further remark that when f (R) = R, the third integral on the right-hand side of the equation above vanishes and hence we recover the typical expression obtained in the pure GR scenario [5,6,9,12,17,18,20]. However, notice that even in the exterior region of an electrically charged compact star, where ρ = 0, the above expression yields an extra mass contribution due to the non-trivial behaviour of the Ricci scalar.…”
Section: As a Consequence Bearing In Mind Thatsupporting
confidence: 81%
See 1 more Smart Citation
“…[45]. We further remark that when f (R) = R, the third integral on the right-hand side of the equation above vanishes and hence we recover the typical expression obtained in the pure GR scenario [5,6,9,12,17,18,20]. However, notice that even in the exterior region of an electrically charged compact star, where ρ = 0, the above expression yields an extra mass contribution due to the non-trivial behaviour of the Ricci scalar.…”
Section: As a Consequence Bearing In Mind Thatsupporting
confidence: 81%
“…Additional results on the impact of electric charge on the global properties of compact stars can be found in Refs. [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the presence of charge affects the rate of gravitational collapse, luminosities, stellar masses and other physical features. Some recent examples of charged static stars and their interesting properties are given in [1][2][3][4][5][6]. In radiating stars, the radial pressure at the stellar boundary is nonvanishing [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We shall start by imposing the quasi-homologous condition (46). Then using (119) and ( 120) in (46) we get 4πqA…”
Section: Conformal Motions: Exact Solutionsmentioning
confidence: 99%